Potential relevance of differential settlements in earthquake-induced liquefaction damage assessment - Fernando Gómez-Martínez (2018)
The assessment of vulnerability of buildings subjected to earthquake-induced liquefaction requires the definition of an integrated damage scale accounting both for ground motion damage and ground permanent movements, which cause rigid-body settlement and tilt of the building but also flexural demand on members due to differential settlement of pad footings. Nevertheless, most of the existing procedures for the estimation of differential settlements rely only in soil characteristics, thus neglecting the influence of building stiffness on the soil-structure interaction. In the present work, based on simplified modelling of soil-structure variability and on preliminary assumption of force distributions, representative values of members' demand due to differential settlement are proposed. A simple approach relying on the structure-to-soil stiffness ratio and the equivalent soil degradation extent under pad footings is adopted. The methodology is calibrated by means of a parametric linear analysis for a set of planar frames. Relative flexural demand due to differential settlements normalised to the seismic flexural demand are obtained. Results show that their relevance may not be very severe, thus damage assessment of differential settlements could be likely accounted separately from flexural and rigid-body demand.